2004
DOI: 10.1021/bi0354177
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Electron Transfer in Photosystem I:  Accumulation of A0- in A-Side or B-Side Mutants of the Axial Ligand to Chlorophyll A0

Abstract: Photosystem I contains two potential electron transfer pathways between P(700) and F(X). These branches are made up of the electron transfer chain components A, A(0), and A(1). The primary electron acceptor A(0) is a chlorophyll a monomer that could be one or both of the two chlorophyll molecules, eC-A(3)/eC-B(3), identified in the 2.5 A resolution structure. The eC-A(3)/eC-B(3) chlorophylls are both coordinated by the sulfur atom of a methionine. This coordination is highly unusual, as interactions between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 28 publications
1
73
0
1
Order By: Relevance
“…Experiments at room temperature using longer delays permitted observation of primary charge separation and secondary ET. Both YF mutants exhibited trapping times (Ϸ25 ps) and DAS (data not shown) indistinguishable from those of the WT (8), indicating that the rates of energy transfer and initial charge separation are not strongly affected. Thus, neither mutation produced detectable long-range perturbations of core antenna Chls, nor did they inhibit primary charge separation within the RC.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Experiments at room temperature using longer delays permitted observation of primary charge separation and secondary ET. Both YF mutants exhibited trapping times (Ϸ25 ps) and DAS (data not shown) indistinguishable from those of the WT (8), indicating that the rates of energy transfer and initial charge separation are not strongly affected. Thus, neither mutation produced detectable long-range perturbations of core antenna Chls, nor did they inhibit primary charge separation within the RC.…”
Section: Resultsmentioning
confidence: 92%
“…In both WT and PsaA-Y696F PS1, the main feature is the P 700 ϩ bleaching band (Fig. 6A); there is no significant accumulation of a negative band at Ϸ680 nm, attributed to the A 0 Ϫ intermediate Chl (8,22). However, there are indications of such a band in the PsaB-Y676F mutant.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…An intermediate value of 25.0 Å was obtained in the WT membranes, which was offered as evidence for bidirectional electron transfer [26]. Ultrafast transient absorbance measurements showed that the A 0 -minus A 0 difference signal accumulates in both the M688H PsaA and M668H PsaB mutants, indicating that electron transfer from A 0 Á -to A 1 is blocked or slowed on the appropriate branch [30]. However, a recent spin-polarized EPR study shows a transient EPR spectrum, probably due to P 700 Á ?…”
Section: Discussionmentioning
confidence: 88%